MORPHOLOGICAL AND FUNCTIONAL STATE OF ENDOTHELIUM AT PATIENTS WITH CORONARY ARTERY DISEASE AND CHRONIC GLOMERULONEFRITIS - I. I. Topchii; O. M. Kirienko; A. I. Tsygankov; T. M. Bondar; O. M. Schenyavskaya (Український Журнал Нефрології та Діалізу, 2017)
All over the world the increase in quantity of patients with vascular complications of chronic inflammatory diseases of kidneys is marked. The interrelation of morphological and biochemical markers of atherosclerotic lesions were studied in 41 patients with coronary artery disease (CAD) (group 1) and 62 - with CAD and chronic glomerulonephritis (CGN) (group 2). An extracranial carotid artery (CA) status was investigated by duplex ultrasonography. VE-cadherin content determined by ELISA. States of the antioxidant system was evaluated by the concentration of malondialdehyde (MDA) and sulfhydryl groups (SH-groups) in the blood plasma by the photometric method. The levels of nitric oxide stable metabolites – NO2 and total (NO2+NO3) in plasma was determined by the photometric method. There was found that the frequency of CA plaques detection in groups 1 and 2 did not differ (27,6% and 31,0%, respectively), but patients of group 2 were reliably younger. Pronounced VE-cadherin increase (3,6-fold, p <0,01) at the background of the deterioration of renal function (2,24 -fold GFR decrease, and urinary protein excretion reaches (0,200,98) g / day) was observed in group 2. The content of NO2 in group 2 was significantly lower than in controls, and total (NO2+NO3) was increased as compared with control (2,40-fold, P <0,01), and with patients of group 1 (in 1,86-fold, p <0.05). Increase of MDA level in patients of group 2 (2,61-fold, P<0,01) accompanied by reduction of SH groups content – by 25,2% (P <0.05) compared with control. Thus, in patients with combined pathology revealed the most pronounced disorders of endothelial integrity and function, which was worsening by imbalance in the pro-antioxidant system. Accelerated atherosclerotic vascular changes in these patients are probably related to the chronic inflammatory process.